Case of cortical superficial siderosis presenting with corticobasal syndrome - Miyazawa, Naotaka; Hasegawa, Itsuki; Mino, Toshikazu; Takeda, Akitoshi; Hatsuta, Hiroyuki; Yoshizaki, Takahito; Takao, Masaki; Itoh, Yoshiaki (Neurology and clinical neuroscience, 2022)
A 70‐year‐old man presented with slow gait and a clumsy hand on the right side. Neurological examination revealed dystonia and ideomotor apraxia in the right hand. A mask‐like face, rigidity in the right arm, and shuffling gait were noticed. Treatment with L‐dopa had no effect. He was clinically diagnosed with corticobasal syndrome (CBS). Susceptibility‐weighted images of brain magnetic resonance imaging showed low‐intensity areas on the surface of the cerebral cortex, especially on the left parietal lobe, brain stem, and cerebellum, indicating superficial siderosis (SS). Neuropathological examination revealed diffuse hemosiderin deposition over the surface of the brain, including the left parietal lobe. Cerebellar hemorrhage with rupture to the subarachnoid space was noticed. Cortical SS should, therefore, be included in the differential diagnosis of CBS.